Perencanaan Jaringan Long Term Evolution (LTE) Menggunakan Parameter Existing Di Universitas Riau - Tanjung, Andika Syahputra; Febrizal, Febrizal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
This paper proposes Long Term Evolution (LTE) network design using of which is eNodeB parameter data existing supplied by Telkomsel operators in the area of Universitas Riau, Pekanbaru. The design was involved several stages namely data analysis, network planning based on capacity (Capacity Planning), network planning based on area coverage (Planning Coverage)and the final stage of design to do simulation using the software atoll. Based on capacity planning, obtained a maximum capacity of cell is 100.6 Mbps with the coverage area cells 1,001 km2 andradius cells 0.444 km2 so obtained 4 eNodeB. Based on obtained coverage planning, obtained a link budget calculation parameters are planning well enough in accordance with the standards ofquality coverage planning, with extensive coverage area cells 262.8 km2 and radius cells 7.2 km2 so obtained 1 eNode. Universitas Riau have urban morphology with an area of 3.62 km2 and 13.978 subscribers, simulation of design on software atoll generate an average signal level -72.11 dBm.Keywords : LTE, planning capacity, Planning Coverage, Average Signal Level